2016
DOI: 10.1007/s13555-016-0157-y
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetics Use-Related Adverse Events and Determinants Among Jigjiga Town Residents, Eastern Ethiopia

Abstract: IntroductionNon-medicated cosmetics use is very common among the Ethiopian population. However, little is known about these products’ related adverse events. The aim of this study was to assess the prevalence and determinants of cosmetics-related adverse events among Jigjiga Town residents, Eastern Ethiopia.MethodsA community-based cross-sectional study design was conducted in May and June 2014. Semi-structured interviews were used to collect cosmetics use pattern and related adverse events. For assessing dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
27
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 19 publications
(23 reference statements)
9
27
2
Order By: Relevance
“…We could not differentiate between allergic or irritant reactions, but these could account for equal proportions of dermatitis. 33 Consistent with previous findings, 20 we also observed that a substantial proportion of patients had acne (19%) and telangiectasia (14%), probably because of long-term use of products containing steroids, as certain common skin care products contain steroids, [34][35][36][37] which can cause acne. 38 It appeared that more females than males had acne, but the difference was not significant, possibly because of a small number of male subjects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We could not differentiate between allergic or irritant reactions, but these could account for equal proportions of dermatitis. 33 Consistent with previous findings, 20 we also observed that a substantial proportion of patients had acne (19%) and telangiectasia (14%), probably because of long-term use of products containing steroids, as certain common skin care products contain steroids, [34][35][36][37] which can cause acne. 38 It appeared that more females than males had acne, but the difference was not significant, possibly because of a small number of male subjects.…”
Section: Discussionsupporting
confidence: 89%
“…19 In certain regions, the incidence can be as high as 14%. 20 Although we cannot specify the incidence of adverse cutaneous reactions to skin care products in the general population of Guangzhou City, China, the 0.1% frequency among all outpatients in a general dermatology clinic is high enough to draw attention to the safety of skin care products.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of use had also shown a statistically significant association with the occurrence of ADE. Similar findings were reported inside the country where higher frequency of use increased the occurrence of the ADE [27]. This study has clearly shown that the participants who selected their TCs by friends as well as by looking appearance and aroma were at a higher risk to develop an ADE.…”
Section: Discussionsupporting
confidence: 86%
“…The number of participants who reported to have experienced adverse cosmetic events was higher as compared to figures documented in other parts of Ethiopia [21,22] and in other countries such as the Netherlands [23], UK [24], Nepal [25], and Rio de Janeiro [26]. However, a higher figure had also been reported in a study by Bilal et al among residents of Jigjiga town in the same country [27]. This can be explained, partly, by the little priority given to cosmetic use safety evaluations and laboratory assessments in Ethiopia [28,29].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation